Solid-State Synthesis and Thermoelectric Properties of Mg2+xSi0.7Sn0.3Sbm. (5th September 2013) - You, Sin-Wook; Kim, Il-Ho; Choi, Soon-Mok; Seo, Won-Seon
Abstract : Mg2+ x Si0.7 Sn0.3 Sb m (0 ≤ x ≤ 0.2, m = 0 or 0.01) solid solutions have been successfully prepared by mechanical alloying and hot pressing as a solid-state synthesis route. All specimens were identified as phases with antifluorite structure and showed n-type conduction. The electrical conductivity of Mg-excess solid solutions was enhanced due to increased electron concentrations. The absolute values of the Seebeck coefficient varied substantially with Sb doping and excess Mg, which was attributed to the change in carrier concentration. The onset temperature of bipolar conduction was shifted higher with Sb doping and excess Mg. The lowest thermal conductivity of 1.3 W/mK was obtained for Mg2 Si0.7 Sn0.3 Sb0.01 . A maximum ZT of 0.64 was achieved at 723 K for Mg2.2 Si0.7 Sn0.3 Sb0.01 .